Implementation of Sharia Economic Strategy in Halal Tourism Development (Case Study of Cacaban Reservoir, Tegal Regency) - Akbar Firmansyah; Masrukhan (International Journal of Educational and Life Sciences, 2025)
Halal tourism is a rapidly growing sector with significant potential to support local economies and meet the needs of Muslim travelers. This study aims to analyze the implementation of Islamic economic strategies in the development of halal tourism at Waduk Cacaban, Tegal Regency. Using a quantitative approach, this research employs a survey method to measure the factors influencing Muslim tourists' decisions in selecting halal tourism destinations. The results of the linear regression analysis indicate that the availability of halal facilities, location accessibility, and Sharia-based marketing strategies significantly impact tourist satisfaction and loyalty. Furthermore, this study identifies challenges in applying Islamic economic principles, including a lack of awareness among business operators and limited infrastructure. Therefore, optimizing regulations, improving halal facilities, and strengthening marketing strategies are essential to enhance Waduk Cacaban’s competitiveness as a leading halal tourism destination.